Impaired Muscular Fat Metabolism in Juvenile Idiopathic Arthritis in Inactive Disease - Rochette, Emmanuelle; Bourdier, Pierre; Pereira, Bruno; Echaubard, Stéphane; Borderon, Corinne; Caron, Nicolas; Chausset, Aurélie; Courteix, Daniel; Fel, Solenne; Kanold, Justyna; Paysal, Justine; Ratel, Sébastien; et al. (Frontiers in Physiology, 2019)
Objectives: The objective of this study was to evaluate muscular metabolic function in children with inactive juvenile idiopathic arthritis (JIA). Methods: Fifteen children with inactive JIA and fifteen healthy controls were matched by sex, biological age, and Tanner stage. Participants completed a submaximal incremental exercise test to determine their fat and carbohydrate oxidation rates. Results: Between the two groups, heart rate values and carbohydrate oxidation rates were the same, regardless of the relative intensity of exercise. Lipid oxidation rates were lower in JIA patients, regardless of the percentage of VO2 peak (p < 0.05). Respiratory exchange ratios beyond 50% of VO2 peak were higher in patients with JIA (p < 0.05). Respective maximal fat oxidation rates (MFO) for controls and children with JIA were 218.7 ± 92.2 vs. 157.5 ± 65.9 mg.min-1 (p = 0.03) and 4.9 ± 1.9 vs. 3.4 ± 1.2 mg.min-1.kg-1 (p = 0.04). There was no difference between the two groups in heart rate, percentage of VO2 peak, or power of exercise to achieve MFO. Controls reached their MFO at an exercise power significantly higher than did JIA subjects (42.8 ± 16.8 and 31.9 ± 9.8 W, p = 0.004). Conclusions: Children with JIA show metabolic disturbance during exercise, even when the disease is considered inactive. This disturbance is seen in a lower lipid oxidation rate during submaximal exercise.